2014
DOI: 10.5713/ajas.2013.13828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-proline on the Growth Performance, and Blood Parameters in Weaned Lipopolysaccharide (LPS)-challenged Pigs

Abstract: This trail was conducted to study the effect of L-proline on the growth performance, and blood parameter in the weaned lipopolysaccharide (LPS)-challenged pigs. Thirty six pigs (9.13±0.85 kg) were assigned randomly to dietary treatments in a 2×3 factorial arrangement in a 20-d growth assay. Factors were intraperitoneal injection with saline or LPS, and three dietary L-proline supplement levels (0%, 0.5%, or 1.0%). On d 10, blood samples were collected at 3 h after LPS (100 μg LPS/kg body weight [BW]) or saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
(33 reference statements)
5
17
0
Order By: Relevance
“…We found that LPS challenge induced growth retardation, and soy isoflavone help attenuated the inhibition of growth performance by LPS at days 7-14. This was in accordance with previous studies that LPS caused loss of body weight and decrease of feed intake [19,23], while supplementation of genistein or daidzein significantly increased the food intake [24]. Previous studies have also revealed that dietary daidzein supplementation improved ADG, ADFI, and G:F of weaned pigs under porcine reproductive and respiratory syndrome (PRRS) virus challenge [15], while genistein increased ADG and ADFI of weaned pigs postinoculation of PRRS virus [25].…”
Section: Discussionsupporting
confidence: 88%
“…We found that LPS challenge induced growth retardation, and soy isoflavone help attenuated the inhibition of growth performance by LPS at days 7-14. This was in accordance with previous studies that LPS caused loss of body weight and decrease of feed intake [19,23], while supplementation of genistein or daidzein significantly increased the food intake [24]. Previous studies have also revealed that dietary daidzein supplementation improved ADG, ADFI, and G:F of weaned pigs under porcine reproductive and respiratory syndrome (PRRS) virus challenge [15], while genistein increased ADG and ADFI of weaned pigs postinoculation of PRRS virus [25].…”
Section: Discussionsupporting
confidence: 88%
“…In conclusion, treatment of pigs with mold-contaminated feed has adverse effects on growth performance, structure of the intestine (histology, morphology and barrier function), and serum amino acid profile. Glutamate likes other functional amino acids can improve animal health [60] [77] . Dietary supplementation with glutamate partially counteracts the impairments induced by mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Glu effectively regulates oxidative stress and intestinal injury in piglets treated with the mycotoxin deoxynivalenol (DNO) [ 104 ]. Pro supplementation has crucial roles in regulating the proliferation and differentiation of IECs, increasing superoxide dismutase (SOD) activities, and expressions of TJPs [ 105 , 106 ]. Dietary supplementation of Pro exerts advantageous immune-stimulatory functions in the mice immunized with inactivated Pasteurella multocida (Pm) [ 107 ].…”
Section: Amino Acids and Intestinal Inflammationmentioning
confidence: 99%